Methodical going near the elementary training future architects of professionally-oriented computer technologies on basis CAD Allplan - Birillo, I.; Doroshenko, Iu. (Theory and practice of design, 2015)
In the article features are exposed and the methodical going is certain near organization and realization of the elementary training of future architects to the professionally-oriented computer technologies on basis CAD Allplan. The reference thematic structure of the specialized educational course is offered.